2018
DOI: 10.5194/esd-9-879-2018
|View full text |Cite
|
Sign up to set email alerts
|

Climate sensitivity estimates – sensitivity to radiative forcing time series and observational data

Abstract: Abstract. Inferred effective climate sensitivity (ECS inf ) is estimated using a method combining radiative forcing (RF) time series and several series of observed ocean heat content (OHC) and near-surface temperature change in a Bayesian framework using a simple energy balance model and a stochastic model. The model is updated compared to our previous analysis by using recent forcing estimates from IPCC, including OHC data for the deep ocean, and extending the time series to 2014. In our main analysis, the me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 55 publications
1
24
4
Order By: Relevance
“…We cannot rule out the very high value of ECS, but we assign a low probability based on the IPCC 2013 low likelihood for the needed value of AER RF2011. Our empirically based determination of ECS is in good overall agreement with the recent empirical determinations of Lewis and Grünwald (2018) (1.87°C, range of 1.1-4.05°C) and Skeie et al (2018) (2.0°C, range of 1.2-3.1°C) and the slightly older empirically determination reported by Otto et al (2013) (2.0°C, range of 1.2-3.9°C) (all range values are for the 5 th and 95 th percent confidence interval). Nijsse et al (2020) reported a median value of ECS of 2.6°C (range of 1.52-4.05°C) based upon analysis of CMIP6 output tied to the actual climate record.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We cannot rule out the very high value of ECS, but we assign a low probability based on the IPCC 2013 low likelihood for the needed value of AER RF2011. Our empirically based determination of ECS is in good overall agreement with the recent empirical determinations of Lewis and Grünwald (2018) (1.87°C, range of 1.1-4.05°C) and Skeie et al (2018) (2.0°C, range of 1.2-3.1°C) and the slightly older empirically determination reported by Otto et al (2013) (2.0°C, range of 1.2-3.9°C) (all range values are for the 5 th and 95 th percent confidence interval). Nijsse et al (2020) reported a median value of ECS of 2.6°C (range of 1.52-4.05°C) based upon analysis of CMIP6 output tied to the actual climate record.…”
Section: Discussionsupporting
confidence: 88%
“…Four empirical determinations of ECS (our study plus Lewis and Grünwald (2018), Otto et al (2013), and Skeie et al (2018)) and the CMIP6-based estimate of Nijsse et al (2020) are in slight contrast with the 2.3-4.7°C range for ECS (5 th and 95 th confidence interval) published recently by Sherwood et al…”
Section: Ecscontrasting
confidence: 86%
See 1 more Smart Citation
“…The ensemble by Smith et al (2018) has a 16-84% confidence interval for transient climate response of 1.3 to 2.0 K, which translates into a ±1 confidence interval for aerosol ERF of −1.2 to −0.6 W m −2 . Skeie et al (2018) obtain a quantitatively similar relationship between aerosol ERF and transient climate response using an energy balance model.…”
Section: 1029/2019rg000660mentioning
confidence: 99%
“…3.1; Hansen et al 2005). Therefore historical F is a source of systematic uncertainty in estimating , especially on account of anthropogenic tropospheric aerosol forcing (Gregory et al 2002;Myhre et al 2013;Forster 2016;Skeie et al 2018).…”
Section: Introductionmentioning
confidence: 99%